The Role of E-Magazines in Promoting Marine Tourism Destination in Bali Island - Ilham Fayyadh Devitra; Sunarto; Donny Juliandri Prihadi; Asep Agus Handaka; Suryana; Atikah Nurhayati (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: This study aims to analyze the role of E-Magazine in promoting marine tourism destinations in Bali. Method: The method used in this research is descriptive qualitative, with data analysis following the Miles & Huberman approach. Data was collected using questionnaires administered to 30 respondents and surveys conducted with 40 tourist respondents using purposive sampling. The respondents were individuals who had read the e-magazine and had traveled to Bali. The data was processed through data reduction, data presentation, and conclusion drawing, using the 7P marketing mix approach. Result: Based on the data processed through data reduction using the 7P marketing mix approach, the Pelayaran Penuh Warna E-Magazine proved to be highly effective in promoting marine tourism destinations in Bali, with a respondent satisfaction rate of 92.5%. The e-magazine was also effective in delivering comprehensive and transparent information, with 93% of respondents finding the content in the e-magazine useful. Contribution: This study is expected to serve as a reference for travel agencies and similar businesses in building their corporate image by promoting marine tourism destinations.